Protein Kinase C δ (PKCδ) Attenuates Bleomycin Induced Pulmonary Fibrosis via Inhibiting NF-κB Signaling Pathway - Wang, Jun; Sun, Lei; Nie, Yunjuan; Duan, Shixin; Zhang, Tao; Wang, Weiwei; Ye, Richard D.; Hou, Shangwei; Qian, Feng (Frontiers in Physiology, 2020)
Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive and lethal interstitial lung disease characterized by consistent pulmonary inflammation. Although protein kinase C delta (PKCδ) is involved in broad scope cellular response, the role of PKCδ in IPF is complicated and has not been fully defined yet. Here, we reported that PKCδ deficiency (PKCδ-/-) aggravated bleomycin (BLM)-induced pulmonary fibrosis and inflammation. Upon challenge with BLM, the pulmonary capillary permeability, immune cell infiltration, inflammatory cytokine production, and collagen deposition were enhanced in PKCδ-/- mice compared to that in PKCδ+/+ mice. In response to poly(I:C) stimulation, PKCδ deficient macrophages displayed an increased production of IL-1β, IL-6, TNF-α, and IL-33, which were associated with an enhanced NF-κB activation. Furthermore, we found that PKCδ could directly bind to and phosphorylate A20, an inhibitory protein of NF-κB signal. These results suggested that PKCδ may inhibit the NF-κB signaling pathway via enhancing the stability and activity of A20, which in turn attenuates pulmonary fibrosis, suggesting that PKCδ is a promising target for treating pulmonary fibrosis.